2000
DOI: 10.1002/(sici)1097-4660(200005)75:5<353::aid-jctb221>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous recovery of heavy metals and degradation of organic species - copper and ethylenediaminetetra-acetic acid (EDTA)

Abstract: In mixed industrial ef¯uent the presence of metal ions can retard the destruction of organic contaminants and the ef®ciency of recovery of metal is reduced by the presence of the organic species. Results are presented for a copper±ethylenediaminetetra-acetic acid (EDTA) system in which both effects occur. An electrochemical cell alone can be used to recover copper in pH range 1.5±4.5 but is not capable of achieving complete mineralisation of EDTA by anodic oxidation. A photolytic cell alone can achieve the des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 25 publications
0
14
0
2
Order By: Relevance
“…A primeira revisão neste contexto foi publicada por Rajeshwar et al, 1 em 1994, e desde então várias revisões estão sendo publicadas expondo os benefícios do tratamento eletroquímico, 2 na degradação anódica de poluentes, [3][4][5] em processos catódicos, como recuperação de metais, 6,7 são relativamente bem sucedidos, sendo implantados em escala industrial. Isso ocorre porque a maioria dos metais podem ser depositados em um grande espectro de materiais eletródicos e, como o valor agregado do metal é alto, a sua recuperação é viável.…”
Section: Aspectos Geraisunclassified
See 1 more Smart Citation
“…A primeira revisão neste contexto foi publicada por Rajeshwar et al, 1 em 1994, e desde então várias revisões estão sendo publicadas expondo os benefícios do tratamento eletroquímico, 2 na degradação anódica de poluentes, [3][4][5] em processos catódicos, como recuperação de metais, 6,7 são relativamente bem sucedidos, sendo implantados em escala industrial. Isso ocorre porque a maioria dos metais podem ser depositados em um grande espectro de materiais eletródicos e, como o valor agregado do metal é alto, a sua recuperação é viável.…”
Section: Aspectos Geraisunclassified
“…A literatura mostra diversos processos de oxidação de compostos orgânicos sobre materiais semicondutores como, por exemplo, corantes da indústria têxtil, 21,22 poluentes na fase gasosa 23 e até na remoção simultânea de substâncias orgânicas e íons metálicos dissolvidos em meio aquoso. 6,7 Assim, a preparação de eletrodos com misturas de 25 A remoção da aspirina, anti-inflamatório largamente utilizado, em soluções aquosas, foi realizada através da oxidação anódica, empregando eletrodos de PbO 2 , diamante dopado com boro (DDB) e Ti/DDB como ânodos. A completa mineralização da aspirina foi alcançada quando utilizado os eletrodos de DDB e Ti/DDB.…”
unclassified
“…In our previous publications we have reported that a combined photolyticelectrolytic system is required for the successful treatment of mixed wastewater streams in order to comply with the discharge consent levels [8,16,17]. In one of our publications we reported the effects of Cu(II) ion on the photodegradation of 2,4-D [8] and the main aim of this study is to investigate whether the presence of an additional chloride group has any effect on the degradation of chlorophenoxy herbicide, 2,4,5-T.…”
Section: Introductionmentioning
confidence: 99%
“…In one of our publications we reported the effects of Cu(II) ion on the photodegradation of 2,4-D [8] and the main aim of this study is to investigate whether the presence of an additional chloride group has any effect on the degradation of chlorophenoxy herbicide, 2,4,5-T. This manuscript describes the effects of Cu(II), which is frequently present in wastewater, on the photolytic degradation of 2,4,5-T and on the effects of 2,4,5-T on the electrolytic recovery of Cu(II) ions, and optimised a combined photolytic -electrolytic cell system for the simultaneous removal of copper and the degradation of 2,4,5-T as part of studies on the simultaneous recovery of metals and degradation of organic pollutants [8,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The use of electrolysis enables both to destroy the ligands onto anode and to recover metals onto cathode. However, the oxidation of organic matter to the harmless substances onto anode is a complicated task in most cases [11].…”
Section: Introductionmentioning
confidence: 99%